Curcuma roseobracteata sp. nov. (Zingiberaceae), a new species from Thailand and distribution notes on the recently described C. suraponii Boonma - PIYAPORN SAENSOUK; SURAPON SAENSOUK; CHARUN MAKNOI; DANH DUC NGUYEN; THAWATPHONG BOONMA (Society for Indonesian Biodiversity, 2024)
Abstract. Saensouk P, Saensouk S, Maknoi C, Nguyen DD, Boonma T. 2024. Curcuma roseobracteata sp. nov. (Zingiberaceae), a new species from Thailand and distribution notes on the recently described C. suraponii Boonma. Biodiversitas 25: 3368-3375. Curcuma roseobracteata P. Saensouk, Saensouk, Maknoi & Boonma sp. nov., a newly identified species within the Curcuma subgenus Curcuma of the Zingiberaceae family, has been found in the northern and southwestern floristic regions of Thailand, distributed in Mae Hong Son, Tak, and Kanchanaburi Provinces. This new species shares similarities with C. rubrobracteata Škorni?ková, M. Sabu & Prasanthkumar, and C. suraponii Boonma, but differentiated by its lemon yellow rhizome; leaves base broadly cuneate to rounded, or cordate, abaxial surface with scattered hairs; thyrse oblong ovoid; fertile bracts obovate, rose pink with a pale green base; coma bracts inconspicuous, with 1-4 in number; bracteoles apex rounded with short mucronate; filament c. 3 × 6 mm; anther c. 8.5 × 3.5 mm; epigynous glands c. 4.5 mm long; ovary 2.5-3 × 2.5 mm. The new taxon is formally described here, detailing its morphological characteristics, vernacular name, ecology, phenology, and distribution, which includes updates on the presence of C. suraponii, previously recorded only in Tak Province, but now also observed in Mae Hong Son Province. The study includes an IUCN conservation assessment based on recent collections and presents a revised taxonomic key to differentiate the new species from its relatives.